The Effect of Government Spending on Education to Human Capital in ACEH Province - SARTIYAH, .; HARTOYO, Sri; SYAUKAT, Yusman; OKTAVIANI, Rina (Journal of Economic Development, Environment and People, 2017)
This study was conducted to examine the effect of government spending on education, poverty, income per capita and the dummy of the main and newly established regions to education in Aceh Province. The data used in this study are panel data of 23 city districts in Aceh Province from 2008 to 2013. To estimate multiple models of data panels, Common Effect Model and The SYSLIN Procedure 2 SLS Estimation using SAS 9.31 Program are used. The results of the study showed that government spending on education, income per capita in main regions are positively and significantly effect on education, while poverty negatively affects on education in Aceh Province. However, education has a small response to government spending on education in Aceh Province. According to the results of the research, it is recommended for local governments to intensify the service and supervision of education in the newly established regions, specifically in remote areas.